PULMONARY THROMBO-EMBOLISM: DIFFICULTIES ENCOUNTERED IN ESTABLISHING CAUSAL RELATIONSHIP AND EXCLUDING THERAPEUTIC MISMANAGEMENT-A CASE REPORT - Hulathduwa, S. R; Wijesinghe, B. P (International Journal of Research -GRANTHAALAYAH, 2021)
Pulmonary embolism designates blockage of pulmonary arteries by substances moved from elsewhere in the body through the circulation. The commonest form is thromboembolism. The presentation of pulmonary thromboembolism (PTE) is extremely variable from being completely asymptomatic to sudden cardiovascular collapse and death. Shortness of breath, chest pain and haemoptysis are other common presentations. PTE is not a frequently encountered entity in routine autopsy practice. Out of all cases detected at autopsy, approximately fifty percent are not clinically diagnosed or even suspected, making it one of the top pathological entities clinically underdiagnosed or misdiagnosed. The autopsy, therefore remains the gold standard of post-mortem identification of PTE. Autopsy also allows to establish or exclude a clinico-pathologic co-relation between the clinical diagnosis and actual cause established post-mortem. Legal issues will arise as to whether a particular traumatic event has a causal relationship with the cause of death as PTE. Establishment of the cause of death (COD) as PTE, timing of the thrombotic event in relation to an ante-mortem trauma and exclusion of medical negligence on the basis of misdiagnosis and missed diagnosis are some important medico-legal issues encountered by the forensic pathologist. The objective of this case presentation is to elaborate practical difficulties encountered by the pathologist in addressing above medico-legal issues. The death of a 46-year-old male bike-rider from PTE, who died three days after being discharged from the hospital on the 26th day following a traffic accident resulting in multiple rib fractures and severe abdominal trauma which warranted splenectomy is discussed here.